To Fight Against the Defensive Jurisprudence with the New Civil Procedure Code: Yes, We Can! Or Can We? - Gava, Rafael Ambrósio (2016)
In order to reduce their workloads, Brazilian Courts have been landing many precedents that lead to unwarranted restrictions to the right to appeal, thereby belittling the fundamental constitutional right to access to justice. Despite the existence of studies on this "defensive jurisprudence", there are still few who analyze it in the light of the new Civil Procedure Code (Law 13.105/2015), which is about to enter into force. This article aims to evaluate the suitability of the new CPC to remedy this adjudicative problem or at least minimize it. We demonstrated, based on literature and through a deductive argumentative reasoning, that the new procedural law contains a number of specific and general legal clauses which may be used as instruments able to curb the adjudicate "defensiveness. Nonetheless, the achievement of this goal will depend largely on how this legal clauses are to be interpreted and applied.